High quality audit committee-internal auditor relationship – how to establish one? - Osman, Mohammad Noor Hisham; Nahar, Hairul Suhaimi; Zainal Abidin, Zaharuddin (Shanlax International Journals, 2019)
Corporate governance codes and internal auditing standards released around the globe emphasized the importance of high quality audit committee-internal auditor relationship. Accumulating academic research output (eg. Cohen, krishnamoorthy and Wright, 2007; Van-Peursem, 2005) further reinforce the benefits of such relationship towards the firrm’s, particularly in ensuring firrm’s financial reporting quality, utilizing materials grounded in auditing and organizational psychological literature, this paper attempts to (i) conceptually define the quality of audit committee-internal auditor relationships and (ii) suggests practical approaches in ensuring high quality relationship could be established in public listed companies.